MEASURES TO REDUCE THE MICROBIAL CONTENT AND THE NUMBER OF SOMATIC CELLS IN COW MILK - Larionov Gennady Anatolyevich; Dzhanabekov Kumiskali Dzhanabekovich; Semenov Vladimir Grigoryevich; Dzhanabekova Gulmira Kumiskalievna; Lavrentiev Anatoly Yurievich; Mardarieva Natalia Valerievna; Checheneshkina Olesya Yuryevna (Scientific Journal of Pedagogy and Economics, 2020)
The article presents the research results obtained on a commercial dairy farm. Studies on the use of modern domestic means of processing the udder before and after milking have been conducted. For this, two experimental and one control groups were formed in the farms. In the summer and autumn periods, the udder of cows in the experimental groups was treated with specific cleaning means and disinfectants. In the control group, the udder processing by special means was not carried out. Hygiene of the udder was maintained by washing the dugs with warm water, as is common in farms. It was found that the udder treatment of cows with disinfectants leads to a decrease in the number of mesophilic aerobic and facultative anaerobic microorganisms and somatic cells in cow’s milk. Treatment of the udder dugs of cows in the 1st experimental group before milking with Priolit means, after milking with Algavit helped to reduce NMAFAnM in milk. The milk by microbial contamination meets the high requirements of interstate and national standards. The research results obtained in the autumn period confirmed the positive effect of udder treatment with agents on reducing the microbial content of milk. Milk of cows of the 1 and 2 experimental and the 3 control groups in terms of NMAFAnM corresponds to the first grade of the national standard. The number of somatic cells in the summer in the cow’s milk of the 3 control group increased 18.42 times, which confirms the relevance of our research. In the milk of cows of the 2nd experimental group, the number of somatic cells decreased 1.39 times, in the 1st experimental group – 6.25 times, which suggests a good combination of the use of means before and after treatment.